1986
DOI: 10.1111/j.1476-5381.1986.tb10192.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of epithelium on the responsiveness of guinea‐pig isolated trachea

Abstract: This study was designed to investigate the possibility that tracheal epithelium generates a relaxant factor analogous to the endothelial‐derived relaxant factor (EDRF) of vascular tissue. The absence of such a factor following epithelial damage in diseases such as asthma might help to explain the airway hyperreactivity characteristic of such diseases. Removal of epithelium by rubbing enhanced the sensitivity of guinea‐pig isolated tracheal chains to 5‐hydroxytryptamine, histamine, acetylcholine, adenosine, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(113 citation statements)
references
References 22 publications
13
99
1
Order By: Relevance
“…Effects of epithelium removal, if any, on other contractile actions also vary. Contractions produced by one or more of histamine, muscarinic agents, 5-hydroxytryptamine, and K' were slightly increased (either pD2 or E,,, or both) (Flavahan et al, 1985;Barnes et al, 1985;Hay et al, 1986a,b;Raeburn et al, 1986ab;Finnen et al, 1986;Holroyde, 1986), or reduced (this study, cf. Whalley, 1978), or were not affected by epithelium removal (Goldie et al, 1986;Raeburn et al, 1986a, Hay et al, 1986aThompson et al, 1986 and this study).…”
Section: Relaxant Agonistsmentioning
confidence: 98%
See 4 more Smart Citations
“…Effects of epithelium removal, if any, on other contractile actions also vary. Contractions produced by one or more of histamine, muscarinic agents, 5-hydroxytryptamine, and K' were slightly increased (either pD2 or E,,, or both) (Flavahan et al, 1985;Barnes et al, 1985;Hay et al, 1986a,b;Raeburn et al, 1986ab;Finnen et al, 1986;Holroyde, 1986), or reduced (this study, cf. Whalley, 1978), or were not affected by epithelium removal (Goldie et al, 1986;Raeburn et al, 1986a, Hay et al, 1986aThompson et al, 1986 and this study).…”
Section: Relaxant Agonistsmentioning
confidence: 98%
“…Barnes et al (1985) found that indomethacin did not alter a slightly increased sensitivity to acetylcholine in bovine epithelium-denuded tracheae. In guinea-pig trachea Holroyde (1986) found that indomethacin moved histamine dose-response curves to the left in both control and epitheliumdenuded preparations. Hay et al (1986b), also working with guinea-pig trachea, demonstrated that indomethacin was without effect on the sensitivity to histamine but produced the same effect as epithelium removal on the EC50 value of methacholine (that was significantly reduced by a factor of about 2).…”
Section: Relaxant Agonistsmentioning
confidence: 99%
See 3 more Smart Citations